P6.12 Sex and travel: msm utility – location based social networking/dating smart phone application in pakistan. (8th July 2017) - Osama, Muhammad
Abstract : Introduction: GRINDR is an MSM-specific location-based social networking application for smart phones originally developed as a free service in 2009. Study also shows that 6 Million users logon to GRINDR an average of 8 times a day in 2013. Pakistan has population of over 200 Million people, usage of GRINDR is getting very common in MSM population in Pakistan due to availability of smart phones on economical price also availability of economical Internet packages. Studies showed that one in five travellers had casual sex, and 50% of these travellers had unsafe sex. One of the review concluded that at least 30%–35% of MSM now use Internet to find sexual partners. Methods: To review previous studies which conducted outside of Pakistan to see whether these applications may be possible tools to enhance HIV/STI prevention interventions within Men who have sex with Men (MSM) community in Pakistan. Results: Review showed that GRINDR is an efficient and effective tool for the identification of a targeted high-risk MSM population in Los Angeles who are vulnerable to contract HIV/STI. There was no significant difference between using hookup apps and contracting HIV. Conclusion: During travel, GRINDR is overused in MSM population to allow users to find other men through on-line dating services. This experience from these studies encourages venereologists to explore MSM smartphones applications' ability to target specific sub-groups within Pakistan's MSM population who are vulnerable to contract HIV/STI, also there is a need to conduct further studies by using smart phone recruitment approach.